Exploring the Diagnostic Potential of Serum Calprotectin and NOD2 Gene Expression in Distinguishing Crohn’s Disease from Ulcerative Colitis - Ghufran Mazin Abdul Majeed, Mudhar Nazar Mahdi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Accurate differentiation between Crohn’s disease (CD) and ulcerative colitis (UC) is crucial for appropriate disease management. Objectives: To evaluate the diagnostic potential of serum calprotectin and NOD2 gene expression in distinguishing CD from UC and healthy controls. Methods: Serum calprotectin levels and NOD2 expression (delta Ct values) were measured in 25 CD patients, 25 UC patients, and 25 healthy controls. Logistic regression analyses assessed their predictive performance. Results: Serum calprotectin levels were significantly elevated in CD and UC compared to controls, with higher levels in CD. NOD2 expression was upregulated in CD but not UC. Calprotectin robustly predicted both CD (multiple R=0.9967341) and UC (multiple R=0.9899838), while NOD2 expression predicted CD (multiple R=0.9987039) but not UC. Conclusion: Serum calprotectin and NOD2 expression show potential as non-invasive biomarkers for differentiating CD from UC, with calprotectin excelling in both diseases and NOD2 specific for CD